A Pragmatic Study of Apology Strategies in Akan (Twi) - Anane, Job (South Asian Journal of Social Sciences and Humanities, 2022)
As human interact with each other there is propensity of stepping on the toes of one another,  when this happens it is incumbent on the parties involved to try as much as possible to sort out  their differences. One of the most effective ways of breaking this barrier is apologizing. The  person apologizing creates the impression that he is remorseful for the harm caused. The purpose  of the study is to examine the realization of apology speech act, which inclines to be more  situation-dependent and less frequently occurring than other speech acts. It also examines how  the patterns of apology strategies are varied in relation to contextual factors (social status, social  distance, and severity of offence) as used by the Akan (Twi) speakers. Discourse completion  Task (DCT) in a form of interview and role play was chosen for the current study. The  researcher created scenes for the DCT that required apologies based on situations occurring in  real life. The researcher explained the DCT thoroughly to the participants and told them to put  themselves in the situation and render an apology. The findings revealed that some Akan (Twi)  speakers acknowledge responsibility, some tried to justify their actions whilst others shift the  blame on others. It was revealed that some people also combine different strategies when  apologizing.
Keywords: Apology; Strategy; Non-occurrence; Justification; Blaming others